PERLINDUNGAN HUKUM PEMEGANG POLIS TERKAIT PEMBARUAN PERJANJIAN ASURANSI KESEHATAN MANAGED CARE PADA PT.ASURANSI JIWA INHEALTH INDONESIA - , SATRIO WICAKSONO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Renewable term and usage of standard agreements on managed care health insurance which is sold by PT. Asuransi Jiwa Inhealth Indonesia affect certainity of law and protection of policy holders. This research aims to determine the implementation of underwriting for prospective policy holder and renewal of the insurance agreement on health insurance managed care policies which are sold by PT. Asuransi Jiwa Inhealth Indonesia. This research also aims to determine the law protection for policy holders in particular on renewal agreement of health insurance managed care conducted by PT. Asuransi Jiwa Inhealth Indonesia. This reserach is a qualitative research with the normative literature and empirical field study. Research is conducted by library research and field research. Subjects are selected with purposive method. The results of researchshowed that the implementation of underwriting prospective policy holder premiums that covers the implementation of let know your customer principle and the determination of prmium with the principles of adequacy,equity,fairness and competition is accordance with the regulations. PT Asuransi Jiwa Inhealth Indonesia does not guarantee certainity of law regarded renewal process due to usage of optionally renewable policy.